Psychological Problems of the Nurses- Rescuers: The Psychological Problems of the Nurses-Rescuers working at Ambulance Department in Baghdad City - Nabeel M. AL-Dakheely (Institute of Medico-legal Publications Pvt Ltd, 2021)
Objectives: the study aimed to assess the psychological problems among the nurses- rescuers who are workingat ambulance department in Baghdad city, and to determine the relationship between the PsychologicalProblems and some demographic characteristics of sample.Methodology: A descriptive – analytic study that used the technique of assessment was conducted on 200male nurses-rescuers staff who are working at ambulance department in Baghdad city from October 29th2007 to october15th 2008. A questionnaire was constricted to achieve the study objectives, which consistedof two major parts with (71) items. The first parts were the demographic characteristics ,while the secondpart dealing with psychological problems (Acute stress disorder, Phobia, Depression & Post traumaticdisorder) of these Nurses-Rescuers .Data was analysis through the use of the suitable statically methods.Results: The finding of the study showed that most of the NR were suffering from the psychologicalproblems (ASD, Phobia ,Depression ,PTSD),and the results showed that there was significant relationshipbetween psychological problems & age, marital status , educational level ,monthly income , occupation area,years of experience & type of violence. While, there was no significant relationship between psychologicalproblems & family size, residency, training sessions.